2020
DOI: 10.18028/rgfc.v9i3.7522
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes Da Legibilidade Das Notas Explicativas De Companhias Brasileiras

Abstract: O objetivo deste trabalho é investigar os determinantes da legibilidade das notas explicativas das companhias brasileiras abertas. Para isso realizou-se um estudo exploratório com abordagem quantitativa, obtido a partir das demonstrações financeiras padronizadas divulgadas anualmente pelas companhias integrantes do IBrX 50, no período compreendido entre 2010 e 2016. Para mensuração da legibilidade, recorreu-se à Flesch Readability Formula. Utilizou-se da regressão linear múltipla para análise dos dados. Os res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…However, after comparing the samples, it was found that the difference in results, considering the dictionary in Portuguese and English, was not significant. In addition, other studies have also indicated that there are no significant differences, in terms of language, in the Flesch index, which can be used for both English and Portuguese texts (Martins et al, 1996;Gomes et al, 2018;Borges & Rech, 2019).…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…However, after comparing the samples, it was found that the difference in results, considering the dictionary in Portuguese and English, was not significant. In addition, other studies have also indicated that there are no significant differences, in terms of language, in the Flesch index, which can be used for both English and Portuguese texts (Martins et al, 1996;Gomes et al, 2018;Borges & Rech, 2019).…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…Samantha Valentim Telles / Bruno Meirelles Salotti 2018; Borges & Rech, 2019;Silva et al, 2020;Cadorin & Theiss, 2022;Mendes & Lucena, 2022;Souza & Borba, 2022;Sena et al, 2023). The lack of a relationship between readability and information quality, as found by Sena et al (2023), or a firm's disclosure strategy that uses narrative complexity to maintain social legitimacy, as found by Hassan et al (2019), could explain this.…”
Section: Fog Number Of Pagesmentioning
confidence: 99%
“…Recently, readability studies have emerged in other markets using different readability metrics (Ajina et al, 2016;Gomes et al, 2018;Bacha & Ajina, 2020;Hassan et al, 2019;Santos et al, 2019;Borges & Rech, 2019;Monteiro et al, 2020;Silva et al, 2020;Telles & Salotti, 2020;Soepriyanto et al, 2021;Sun et al, 2022;Cadorin & Theiss, 2022;Mendes & Lucena, 2022;Souza & Borba, 2022;Sena et al, 2023). However, these studies do not examine the proximity of readability to understandability.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas com enfoque em análise textual das demonstrações contábeis contribuem com o entendimento da comunicação entre companhias e usuários da informação contábil (Borges & Rech, 2019). Tal afirmativa é confirmada por Li (2008), ao identificar que as características linguísticas das demonstrações contábeis afetam o desempenho das companhias.…”
Section: Introductionunclassified